Pre-Draft Elbow Magnetic Resonance Imaging in Major League Baseball Pitchers (127). Issue 10 (31st October 2021) - Erickson, Brandon; Chalmers, Peter; Dangelo, John; Ma, Kevin; Alexander, Frank; Ahmad, Christopher
Objectives: Evaluate pre-draft elbow MRI on baseball pitchers who were entering the MLB draft to determine the presence or absence of pathology, and the associations between these pathologies and UCL tears, and inter-observer reliability regarding common MRI pathology. Methods: Pre-draft elbow MRI and X-Rays on prospective MLB pitchers between 2011-2017 were deidentified and reviewed by two separate authors. The authors graded the X-Rays MRI on several factors including presence or absence of ulnar collateral ligament (UCL) ossification, UCL appearance (heterogeneous or not), UCL thickening (and location), UCL tear (partial vs. full thickness and location), muscle strain, flexor tendon tear, posteromedial osteophyte, sublime tubercle enthesophyte, and osseous stress reactions. Results: Overall, 245 pre-draft elbow X-Rays and MRI were reviewed. On X-Ray: 12 (4.9%) had ossification within the UCL; 34 (13.9%) had an olecranon osteophyte; 14 (5.7%) had a sublime tubercle enthesophyte. MRI abnormalities were found in 70% (171/245) of pitchers. UCL thickening was found in 20% of pitchers. Regarding UCL tears, 3% had a full thickness tear and 24% had a partial thickness tear. Of full thickness tears, 86% were distal and one was midsubstance. Of partial thickness tears, 41% (24/58) were distal, 12% (7/58) were midsubstance, and 47% (27/58) were proximal. Periligamentous edema was present in 36% of pitchers while 14% had a flexor pronator muscle strain. Stress reactions were seen in 27% and most commonly involved the sublime tubercle. Based upon the presence of periligamentous edema, distal UCL pathology was more likely to be chronic than acute while proximal UCL pathology was more likely to be acute. Conclusions: The majority (70%) of pitchers entering the MLB draft had abnormal findings on their MRI, most commonly involving changes to the UCL. Interobserver reliability was acceptable following definition of pathology when reading pre-draft elbow MRI on MLB prospects.